SIMULTANEOUS ANALYSIS OF THE BIOACTIVE COMPONENTS OF AN EXTRACT OF YEONGGYECHULGAM-TANG, A TRADITIONAL HERBAL PRESCRIPTION, USING HPLC–DAD - Seo, Chang-Seob; Shin, Hyeun-Kyoo (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Yeonggyechulgam-tang (YGCGT) is a well-known classic herbal formula and has been used clinically in Korea for the treatment of chest congestion. High-performance liquid chromatography (HPLC) analytical method coupled with diode-array detection (DAD) was performed for the simultaneous analysis of eight bioactive components, liquiritin apioside, liquiritin, coumarin, liquiritigenin, cinnamic acid, cinnamaldehyde, glycyrrhizin, and atractylenolide III in a YGCGT decoction. Materials and Methods: For simultaneous analysis using HPLC, the eight components were separated using a Phenomenex Gemini C18 column (250 mm  4.6 mm; particle size 5 m) eluted with a gradient of 0.1% (v/v) aqueous trifluoroacetic acid and acetonitrile at 1.0 mL/min. The column temperature and injection volume were 40C and 10 L. Results: Correlation coefficients of the eight compounds ranged between 0.9996 and 1.0000. The lower limits of detection and quantification of the analytes were 0.01–0.09 and 0.02–0.28 g/mL, respectively. Recovery of the eight compounds was 97.63–102.70% and the relative standard deviation (RSD) was less than 3.00%. The RSDs of intra and interday precision were 0.06–2.07% and 0.02–1.95%, respectively. The amounts of the eight compounds in a lyophilized YGCGT were in the range 0.18 to 10.34 mg/g. Conclusion: The optimized and validated HPLC analytical method used in the present study is expected to be useful for evaluation the quality of YGCGT decoctions or related herbal prescriptions.